Super nós em sistemas P2P de distribuição de mídia ao vivo - Joao Ferreira D' Arauto e Oliveira (2010)
In the past few years live streaming networks have become a killer application over the Internet.Use peer-to-peer (P2P) networks to broadcast live content has some advantages such as scalability in number of users, fault tolerance and cost reduction, however, problems relating to safety and quality of both the network and the content contribute to low usage of that technology in a daily basis.In this work the study of P2P live streaming networks has led to identification of a particularly important element in the network, the super node. Focusing on this feature we held discussions, studies and proposals over the potential of the super node, its appearance and how to use this in order to create topologies which reduces the negative effects of using P2P.The results presented here especially show the extensive influence of the super nodes on the safety and quality of service of the overlay. Experiments in real environment showed that a single super node can influence network's download bandwidth over 30% and over 50% of all users. This characteristic associated with content pollution would be disastrous for the system. In simulation it was observed that a two-layered topology, being one composed of preset super nodes, is able to reduce latency and to increase the stream continuity in situations of high churn. Besides, it is able to more than halve the average amount of network's pollution traffic for a combined attack of 10% of participants compared to the original layout.Thus, we believe that the proposed architecture can be valuable and successfully applied to next generation P2P live streaming systems.